Targeting pulmonary vascular endothelial cells for the treatment of respiratory diseases - Li, Yi-Xuan; Wang, Hong-Bo; Li, Jing; Jin, Jian-Bo; Hu, Jing-Bo; Yang, Chun-Lin (Frontiers in Pharmacology, 2022)
Pulmonary vascular endothelial cells (VECs) are the main damaged cells in the pathogenesis of various respiratory diseases and mediate the development and regulation of the diseases. Effective intervention targeting pulmonary VECs is of great significance for the treatment of respiratory diseases. A variety of cell markers are expressed on the surface of VECs, some of which can be specifically combined with the drugs or carriers modified by corresponding ligands such as ICAM-1, PECAM-1 and P-selectin, to achieve effective delivery of drugs in lung tissues. In addition, the great endothelial surface area of the pulmonary vessels, the “First pass effect” of venous blood in lung tissues, and the high volume and relatively slow blood perfusion rate of pulmonary capillaries further promotes the drug distribution in lung tissues. This review summarizes the representative markers at the onset of respiratory diseases, and drug delivery systems designed to target these markers and their therapeutic effects.